A LETHAL CASE OF SEVERE CARBIMAZOLE-INDUCED AGRANULOCYTOSIS - Hidayah, WY Wan Nur; Sanaa, WA Siti; Hanuni, MA Masliza (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Agranulocytosis is a severe complication of carbimazole, the primary drug for treating hyperthyroidism. It is rare with an incidence rate of 0.3–0.6% and mortality rate of 21.5%. Onset may develop within 7 days of initiation of anti-thyroid drug therapy. This case report highlights the deleterious effect of carbimazole-induced agranulocytosis in an elderly female. CASE A 70-year-old female with newly diagnosed hyperthyroidism (baseline TSH: 0.002 m IU/L, free T4: 58 pmol/L) was initiated on carbimazole 30 mg once daily at a health clinic. After approximately one month on carbimazole, she developed fever, sore throat, and multiple oral ulcers. On examination, she exhibited a spiking temperature of 39.4°C, injected throat, multiple oral ulcers over the hard palate, tongue, and lower lip, and a diffuse goitre. She had leucopoenia with total white blood cell count of 1.0, with immeasurable absolute neutrophil count (ANC) and no blast cells. Repeat TSH was 0.003 m IU/L and fT4 was 39.55 pmol/L. Chest radiograph showed consolidation over the right lower lung zone. Initial treatment included intravenous piperacillintazobactam, subcutaneous granulocyte colony-stimulating factor (G-CSF) 300 mcg daily, cholestyramine, Lugol’s iodine, and propranolol. Due to the deterioration in her clinical condition, we promptly escalated her antimicrobials to meropenem, micafungin and increased her G-CSF dosing to 300 mcg two times a day. Her ANC remained at 0.01- 0.02 (109 /L). Despite treatment escalation, she succumbed to severe sepsis after 8 days of admission. CONCLUSION The primary treatment for carbimazole-induced agranulocytosis involves discontinuing the offending drug and administering intravenous broad-spectrum antibiotics. G-CSF may be used to expedite haematological recovery. Clinical vigilance is crucial when initiating carbimazole, especially in high-risk patients such as the elderly and those receiving high doses initially, by conducting early repeat blood investigations. This approach enables early intervention to mitigate adverse outcomes and ensure a favourable prognosis.